Research on 3D Target State Estimation Technology of Helicopter Fire Control System - Tian, Jia; Zhai, Mo; Zhang, Zhiqi; Chen, Hongzheng; Sheng, Shouzhao (2023 2nd International Conference on Artificial Intelligence and Computer Information Technology (AICIT), 2023)
In view of the inaccuracy of target state estimation in helicopter high maneuvering flight and the fact that a single model can not cover all maneuvering forms of the target, considering the timeliness and accuracy of the solution of the fire control system, the target model selected by the Interacting Multiple Model must be simple enough. An interacting multiple model algorithm based on constant velocity, constant acceleration and coordinated turning motion model are proposed in this paper. The algorithm is combined with the smoothing algorithm to improve the reliability and accuracy of maneuvering target state estimation, and the extended Kalman filter is used to improve the adaptive ability and robustness of the algorithm. The simulation results show that the three-dimensional target state estimation technology based on interacting multiple model smoothing algorithm improves the accuracy and reliability of target state estimation and has good practical application value.